Occurrence and Classification of Cerebrovascular Events after Isolated Bioprosthetic Surgical Aortic Valve Replacement: A Competing Risk Analysis of the CAREAVR Study - Joonas Lehto; Markus Malmberg; Fausto Biancari; Juha Hartikainen; Leo Ihlberg; Fredrik Yannopoulos; Teemu Riekkinen; Anna Nissfolk; Samuli Salmi; Maunu Nissinen; Juhani Airaksinen; Tuomo Nieminen; et al. (United States, 2022)
Background: The long-term incidence of stroke and the proportion of cardioembolic events after bioprosthetic surgical aortic valve replacement (SAVR) remain largely unknown.
Methods: The CAREAVR study sought to assess the rate of stroke and transient ischemic attack (TIA) in patients who underwent isolated surgical aortic valve replacement with a bioprosthesis at four Finnish university hospitals between 2002 and 2014. Data was collected retrospectively and included 721 patients. Median follow-up time was 4.8 [3.0–7.0] years.
Results: At 5 years, freedom from stroke was 89.0%, from TIA 94.1%, and from stroke and TIA 83.7%. The median time between index procedure and stroke or TIA was 1.7 years [29 days–3.9 years]. Stroke was of cardioembolic origin in 44.4% of patients. In multivariable competing risk analysis, increased age (HR 1.03, 95%CI 1.00–1.06, p = 0.022), previous stroke or TIA (HR 1.75, 95%CI 1.14–2.70, p = 0.010), New York Heart Association (NYHA) class III or more (HR 1.51, 95%CI 1.01–2.24, p = 0.044) and insulin treatment at discharge (HR 1.20, 95%CI 1.09–3.64, p = 0.024) were independent predictors of stroke or TIA. Cerebrovascular events occurred in 47.2% of patients with ongoing anticoagulation therapy.
Conclusion: In this study, the incidence of stroke in the early postoperative period after bioprosthetic SAVR was higher than previously documented. Almost half of strokes were of cardioembolic etiology. These findings highlight the need for the better prevention strategies for cardioembolic events after bioprosthetic SAVR.